Faktor yang Mempengaruhi Persepsi Kemudahan dan Kemanfaatan Penggunaan Sistem Informasi Manajemen RSU Kaliwates Jember Tahun 2019 - Famela Niken Arista Furi; Christiyana Sandra; Eri Witcahyo (UPT Percetakan dan Penerbitan Universitas Jember, 2021)
Kaliwates General Hospital is a privately owned public service body with full accreditation status for five services and was established by the Ministry of Health of the Republic of Indonesia on December 31, 2010, No.Y.M.01.10/III/7957/10. At the beginning of its development, Kaliwates General Hospital managed data and information using still manual systems. In 2012 Kaliwates General Hospital began using computerized management information systems and changed vendors in 2015. This research is an analytical study with an observational approach. In this study, researchers tested hypotheses on the influence of institutional factors, social factors, and individual factors independently and together influenced the perceived ease and prestige of the usefulness of information systems. Institutional factors, social factors, individual factors, and ease of use significantly affect perceived usefulness in the Kaliwates general hospital management information system.